CHILD COMMUNICATION AND MORAL CULTIVATION FOR CHILDREN - Nanang Susianto; Mailin Mailin; Ahmad Muhajir; M. Zainuddin Daulay (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
Reading the Al-Qur’an is one way to acquire glory and primacy on the side of god communication is an important part of human life. So too is harmonious communication a desirable situation in the family. The family also has an important role to play in the development of a child's character, especially the morals of each child. Teaching children morality early on helps them socialize in families, neighborhoods, schools, and communities. Consistent with what is taught, children become accustomed to behaviors that reflect religious values. Implanting values and moral materials should go hand in hand by instilling virtue and overbearing children in moral behavior. This study is intended for us as parents to know what communication a child wants to have and how parents' role in instilling moral values is to make children have good character. Research methods use qualitative research methods. Research indicates that children's communication that should be understood by parents is important to children. In the cultivation of moral values also parents cannot follow the same manner of speaking or communication as their fellow adults. For when implanting value to children, parents must choose a young vocabulary that is understood and understood by the child